The Demographic Dividend in Latin America: The Economic Effect of Changes in the Age Structure of Populations - Pinto Aguirre, Guido (2015)
¾    The demographic dividend is the potential economic growth created by changes in the age distribution of a population. As fertility declines steadily over several decades, the population’s age distribution shifts from a youthful age structure to one dominated by a large group of working-age young adults. This provides a window of opportunity for a bigger economic growth and a reduction in poverty. That is, as the relative size of the labor force increases, the country’s output expands because there are simply more workers and producers. However, this window of opportunity is not automatic and can be rather short-lived. Thus, economic, social, and governance policies are needed to prepare a favorable landscape for the uptake of a large workforce into the more-productive sectors. Strategic investments in human capital (education and health) are required to respond adequately to the expanding economic opportunities. Many Latin American countries have already begun to realize the demographic dividend. The region has shown consistent economic growth during the last decade, thus creating favorable conditions to absorb an ever-growing labor force of young adults.